2022
DOI: 10.3389/fonc.2022.907076
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral Imaging Manifestations on Gd-EOB-DTPA-Enhanced MRI for Preoperative Prediction of Microvascular Invasion in Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis

Abstract: PurposeThe aim was to investigate the association between microvascular invasion (MVI) and the peritumoral imaging features of gadolinium ethoxybenzyl DTPA-enhanced magnetic resonance imaging (Gd-EOB-DTPA-enhanced MRI) in hepatocellular carcinoma (HCC).MethodsUp until Feb 24, 2022, the PubMed, Embase, and Cochrane Library databases were carefully searched for relevant material. The software packages utilized for this meta-analysis were Review Manager 5.4.1, Meta-DiSc 1.4, and Stata16.0. Summary results are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…6). According to a meta-analysis, the pooled sensitivity and specificity of peritumoral arterial enhancement were 0.50 and 0.80, respectively, whereas these values for peritumoral hypointensity during the HBP were 0.55 and 0.87, respectively 19 . Thus, GA-MRI exhibits poor sensitivity, but good specificity for the identification of MVI.…”
Section: Clinical Significance Of Focal Liver Lesionsmentioning
confidence: 99%
“…6). According to a meta-analysis, the pooled sensitivity and specificity of peritumoral arterial enhancement were 0.50 and 0.80, respectively, whereas these values for peritumoral hypointensity during the HBP were 0.55 and 0.87, respectively 19 . Thus, GA-MRI exhibits poor sensitivity, but good specificity for the identification of MVI.…”
Section: Clinical Significance Of Focal Liver Lesionsmentioning
confidence: 99%
“… 54 , 55 Previous work has shown that HBP peritumoral hypointensity is highly correlated with MVI. 55 , 56 Kim et al 55 suggested that HBP peritumoral hypointensity without associated signal intensity changes on non-HBP sequences represents the change in function of hepatocytes surrounding the tumor. This explains why this imaging finding has a high specificity yet low sensitivity for MVI, as altered hepatocyte function is thought to occur later in the course of MVI development and expansion.…”
Section: Prognostic Imaging Featuresmentioning
confidence: 99%
“…In addition to better detection of nodules, in particular with hepatic arterial phase hypoenhancement and hypointensity on HBP acquisitions, HBP images have prognostic value in patients with HCC. Marked hepatobiliary phase hypointensity is correlated with HCC aggressiveness [19], and peritumoral hypointensity is associated with the presence of microvascular invasion (MVI) [20,21]. A recent meta-analysis has also reported an increased risk of tumor recurrence after resection or LT in the presence of hypointense HCC on HBP acquisitions [19].…”
Section: The Added Value Of the Hepatobiliary Phasementioning
confidence: 99%
“…The imaging features associated with MVI include nonsmooth tumor margin [78], incomplete tumor capsule [79], low ADC, large size, peritumoral APHE, and peritumoral HBP hypointensity [80]. Peritumoral hypointensity on HBP is the MRI feature that is most suggestive of MVI and can be useful to confirm MVI [21]. Numerous prognostic nomograms or feature clusters have been proposed to predict MVI [81][82][83].…”
Section: Imaging Of Microvascular Invasionmentioning
confidence: 99%